The Effectiveness of STEM-Based Android-Based Learning Media on Students' Critical Thinking Skills - Irfana, Shiva; Hardyanto, Wahyu; Wahyuni, Siti (Physics Communication, 2022)
PISA data shows that the critical thinking skills of 21st century students are still at a low level. The 21st century requires students to be able to integrate technology in learning activities. Android-based learning media is an alternative learning media that is integrated with technology. Science, Technology, Engineering, and Mathematics (STEM) is an integrative approach that can improve critical thinking skills. This study aims to analyze the effectiveness of Android-based learning media with the STEM approach to improve students' critical thinking skills. The study used Research and Development (RD) method, namely introduction, media validation, and media testing. The subject of this research is class X vocational school majoring in motorcycle engineering and business. Data collection techniques used research instruments with quantitative data analysis. The data collection instrument was given through a written test in the form of essay questions that included aspects of critical thinking skills. The results of this study indicate that the results of the n-gain mean the pretest and posttest values was 0.77 with high criteria. Aspects of critical thinking skills that make a major contribution were aspects of evaluation and conclusion. Based on the results of the study, it can be concluded that Android-based learning media with the STEM approach is effective in improving creative thinking skills.